Metronidazole Tablet Menyebabkan Perubahan Warna Urine: Laporan Kasus - Arrang, Sherly Tandi (JFIOnline | Print ISSN 1412-1107 | e-ISSN 2355-696X, 2020)
Cases of urine discoloration after the use of metronidazole are still rarely found or reported. A female patient (38 years old) experienced vaginal discharge and was given metronidazole therapy. Urine color of the patient was to be reddish in few hours after taking metronidazole tablet . Correlation between metronidazole tablet and urine discoloration was review by Naranjo scale. Based on the assessment of adverse drug reaction probability scale (Naranjo Scale) that consists of 10 questions, total score for this report was seven (7) or probable, which means that metronidazole associated with reddish urine. Urine discoloration to be darken or reddish due to pigmentation by metabolites of metronidazole. Metronidazole associated dark urine/reddish urine and urine color -return to normal after the medicine is stopped.